Empowering Poor Communities through Decentralized Decision Making : The Vietnam Community Based Rural Infrastructure Project - World Bank (Washington, DC, 2012)
Vietnam made remarkable progress in poverty reduction in the 1990s. Poverty rates decreased from 58% to 37% between 1993 and 1998. The reduction in poverty rates among indigenous people (who constitute 13% of the population and mostly live in remote areas) has been less remarkable. During the same period, the poverty incidence has gone down from 84% to 75%, leaving their poverty rates more than twice as high as that of the majority group, i.e. the Kinh group. In response, the Government has initiated several targeted poverty reduction programs to reduce poverty. One of these is "Program 135" to support mountainous and remote communes. Communes, which are clusters of villages, are the lowest level of government or local administration in Vietnam. Program 135 was established in 1998 to provide resources to more than 1,700 of the poorest communes for small infrastructure improvements and capacity building of local governments. The Community Based Rural Infrastructure Project (CBRIP) builds on the Government's initiative, but offers a somewhat different approach to infrastructure development - one that is more demand driven and promotes a greater role in decision making by beneficiaries.